Students' Perceptions of Teacher Professional Competence: How Does It Correlate with Elementary School Student Learning Achievement? - Ila Israwaty; Nurqalbi Ramadhani; Wawan Krismanto (Pedagogik Journal of Islamic Elementary School, 2025)
This research aims to determine the correlation between students' perceptions of Teacher Professional Competence (TPC) and science learning achievement. This research is a quantitative approach with correlation research. The population is 107 students, and there is a sample of 85 students in 5th grade at SD Negeri 3 Parepare, South Sulawesi. Data collection used student perception questionnaires about TPC and student learning achievement tests. The data analysis techniques are correlation analysis and significance testing. The results show that students' perceptions of TPC are relatively high. Apart from that, students' science learning achievements are classified as good. From the results of the correlation analysis, the sig value is obtained. 0.002 ˂ 0.05 or H0 is rejected, and H1 is accepted, with a correlation coefficient value of 0.328. The conclusion is that a significant positive correlation exists between students' perceptions of TPC and science learning achievement.